2017
DOI: 10.2320/matertrans.y-m2017833
|View full text |Cite
|
Sign up to set email alerts
|

Powder Forming Process from Machined Titanium Chips via Heat Treatment in Hydrogen Atmosphere

Abstract: The recycling process of the coarse machined chips from the commercial Ti-6%Al-4%V (Ti-64) alloy products to ne powders available for powder metallurgy (PM) components was established. The brittle TiH 2 compounds formation in Ti chips via heat treatment in hydrogen gas atmosphere signi cantly improved their milling ability. TG-TDA and XRD analysis suggested the hydration and dehydration behavior of pure Ti and TiH 2 powders. The suitable hydration temperature over 873 K in H 2-Ar mixed gas successfully caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…When sintering was performed in the mixed gas of Ar + H 2 , another phase, TiH 2 , was observed with weakened reflections from the main components of the composite. This hydriding reaction is expressed as follows 28 Ti H TiH…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When sintering was performed in the mixed gas of Ar + H 2 , another phase, TiH 2 , was observed with weakened reflections from the main components of the composite. This hydriding reaction is expressed as follows 28 Ti H TiH…”
Section: Resultsmentioning
confidence: 99%
“…During cooling, a part of TiH 2 was decomposed to Ti and H 2 . 28 As a result, the reflection from the titanium matrix phase was lowered. Another reason for the change in the peak intensity could be related to the transition from β-Ti to α-Ti during cooling because of the higher hydrogen diffusion rate in β-Ti atoms than that in α-Ti atoms, which will broaden the stability region of the β-Ti phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors revealed the success of applying a pre-heat treatment on a Ti alloy, heating in an H 2 -Ar mixture atmosphere, on decreasing particle size, the production of fine particles was attributed to the formation of brittle TiH 2 compound during the pre-heat treatment step [ 26 ]. Another study evaluated the effect of chemical composition on fragmentation, the application of similar milling conditions on two steels, an extra low carbon steel and a low carbon type, the former type faced with agglomeration formation caused by cold welding.…”
Section: Characterization Of Powder Particles Produced From Metal Chipsmentioning
confidence: 99%